Missing Data in Econometric Estimation - Drettakis, E. G. (Review of Economic Studies, 1973)
Journal Article Missing Data in Econometric Estimation Get access E. G. Drettakis E. G. Drettakis University of Leeds Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 4, October 1973, Pages 537–552, https://doi.org/10.2307/2296587 Published: 01 October 1973